Coercive Coverage? A Study of Media Influence on U.S. Foreign Policy Towards Sierra Leone. - Yohannes, Keren I. (Tufts Archival Research Center, 2014)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: United States’ foreign policy responses to the Sierra Leone civil war fluctuated dramatically over the eleven-year war. Policies ranged from logistical and financial support for multilateral and British interventions to humanitarian relief and culminated with the U. S. becoming the biggest financial supporter of post-conflict truth and reconciliation processes. A question remains, however, as to what national, geopolitical, and humanitarian factors influenced U.S. policymakers’ decisions. This study addresses media influence as a potential influence on U.S. responses to the war. Using the concept of the CNN effect, which suggests that media can determine foreign policy decisions under certain conditions, I complete an empirical analysis of the relationship between media and the U.S. policy decisions to support the creation of a U.N. peacekeeping mission and the mission’s later expansion during the height of the crisis in 1999 and 2000. The study expands the pool of literature on the CNN effect by providing among the first empirical analyses of the media-policy relationship in regards to the Sierra Leone civil war. For each decision, I consider media influence in relation to other factors relevant to U.S. policymaking, including U.S. national interests, the conflict’s timing, and the relationship of the U.S. to the U.N.